2021
DOI: 10.1158/1078-0432.ccr-20-3362
|View full text |Cite
|
Sign up to set email alerts
|

Improved Detection of Postoperative Residual Meningioma with [68Ga]Ga-DOTA-TOC PET Imaging Using a High-resolution Research Tomograph PET Scanner

Abstract: Purpose: PET with somatostatin receptor ligand [ 68 Ga]Ga-DOTA-D-Phe 1 -Tyr 3 -octreotide ([ 68 Ga]Ga-DOTA-TOC) is an established method in radiotherapy planning because of the improved detection and delineation of meningioma tissue. We investigated the diagnostic accuracy of supplementary [ 68 Ga]Ga-DOTA-TOC PET in patients with a 3-month postoperative MRI reporting gross-total resection (GTR).Experimental Design: Thirty-seven patients with a histologically proven meningioma and GTR on postoperative MRI were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…One study correlating 68 Ga DOTATATE PET with intraoperative sampling showed greater sensitivity as compared to contrast enhanced MRI (92.3% vs 79.5% for primary and 88.1% vs 76.7% for recurrent tumors). Remarkably, in another study by Bashir et al [ 74 ], residual [ 68 ] Ga-DOTATOC PET uptake was noted after gross total resection of 23 of 37 (62%) meningiomas, as determined by standard of care MRI. Of these 23, nine (39%) were confirmed either by subsequent recurrence, or by sampling during re-operation.…”
Section: Future Directionsmentioning
confidence: 90%
“…One study correlating 68 Ga DOTATATE PET with intraoperative sampling showed greater sensitivity as compared to contrast enhanced MRI (92.3% vs 79.5% for primary and 88.1% vs 76.7% for recurrent tumors). Remarkably, in another study by Bashir et al [ 74 ], residual [ 68 ] Ga-DOTATOC PET uptake was noted after gross total resection of 23 of 37 (62%) meningiomas, as determined by standard of care MRI. Of these 23, nine (39%) were confirmed either by subsequent recurrence, or by sampling during re-operation.…”
Section: Future Directionsmentioning
confidence: 90%
“…Twelve articles were retrieved for full-text review. After exclusion of the studies 19 , 20 , 21 , 22 , 23 , 24 , 25 that did not provide data for tumor grade and also did not allow the calculation of diagnostic accuracy, five cohort studies were considered eligible for our analysis. 3 , 4 , 26 , 27 , 28 These five studies included 242 patients with a total of 196 low-grade (Grade 1) and 46 high-grade (Grade 2/3) meningiomas.…”
Section: Resultsmentioning
confidence: 99%
“…Somatostatin receptor PET imaging has been shown to be highly sensitive in detecting tumor remnant after microsurgical tumor resection in patients with intracranial meningioma [ 23 , 25 ]. However, the prognostic importance of residual tumor as indicated by [ 68 Ga]Ga-DOTA-TATE PET/CT is so far unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Somatostatin receptor type 2 (SSTR2) is ubiquitously expressed in up to 100% of meningiomas and can be addressed by radiolabeled SSTR2 ligands such as [ 68 Ga]Gallium-DOTA-TATE, [ 68 Ga]Gallium-DOTA-TOC, and most recently [ 18 F]SiTATE [ 18 , 19 ]. Biopsy-controlled studies have validated SSTR2 PET/CT as a highly sensitive tool for detecting meningioma tissue and distinguishing between tumor and tumor-free tissue, which is superior to MRI [ 20 23 ]. This enables differential diagnosis of MR morphologically ambiguous lesions [ 24 ], provides an excellent opportunity to assess the extent of resection after surgery [ 23 , 25 ], and importantly also improves tumor delineation for radiation planning [ 26 – 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation